Analisis Pengaruh Daya Tarik dan Amenitas Terhadap Referensi Kunjungan Wisata di Desa Wisata Cemagi, Kabupaten Badung - Dewi, Desak Made Purnama; I Nyoman, Widana (Jurnal Mosaik Hospitaliti, 2025)
This study aims to analyze the influence of tourist attractions and amenities on tourist decision-making in choosing Cemagi Tourism Village as a travel destination. A quantitative approach was applied using a survey method, with 100 respondents selected through accidental sampling. Data were analyzed using multiple linear regression. The findings indicate that both tourist attraction and amenities significantly and positively affect the visit decision, both partially and simultaneously. Amenities emerged as the most dominant factor influencing tourist preferences. These results underscore the importance of managing tourism facilities and key attractions to enhance visits to culturally-based tourism villages.